2019
DOI: 10.1080/02640414.2019.1705541
|View full text |Cite
|
Sign up to set email alerts
|

Specific types of sports and exercise group participation and socio-psychological health in older people

Abstract: Older people who engage in sports and exercise in a group render greater benefits for sociopsychological aspects compared to exercising alone. The aim of this study was to identify the prevalence of specific types of sports and exercise groups and the association with self-rated health, depressive symptoms, and frequency of laughter among community-dwelling older people. We used cross-sectional data from the 2016 Japan Gerontological Evaluation Study and analysed 63,465 males and 68,497 females aged ≥65 years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 33 publications
5
25
0
2
Order By: Relevance
“…Our results are aligned with two other studies that suggested that older women who participated in a walking group had higher SRH statuses compared to women who walked on their own [66,67]. In an additional study, engagement in group sports activities (specifically golf and walking) was significantly related to excellent selfrated health [68]. In a further study, Russell and Chase (2019) found that participation in social activities was inversely associated with sedentary behavior and multiple dimensions of health statuses [69].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results are aligned with two other studies that suggested that older women who participated in a walking group had higher SRH statuses compared to women who walked on their own [66,67]. In an additional study, engagement in group sports activities (specifically golf and walking) was significantly related to excellent selfrated health [68]. In a further study, Russell and Chase (2019) found that participation in social activities was inversely associated with sedentary behavior and multiple dimensions of health statuses [69].…”
Section: Discussionsupporting
confidence: 89%
“…This finding is in line with Doré et al [74], who found that team sport and informal group participation in physical activity was not significantly associated with depressive symptoms. In contrast, a massive body of literature suggests negative associations between participation in team or group sports and depressive symptoms [68,75,76].…”
Section: Discussionmentioning
confidence: 95%
“…Based on previous studies, older populations, especially in rural areas, have difficulties interacting with others, which can negatively affect their health and increase depression and feelings of social isolation [20,26,27]. As smiling is an essential factor for the improvement of QOL, future studies should clarify the relationships between smiles and recreational activities, such as community activities that aim to keep older people active and motivated to live healthily [28]. The clarification of the quality of smiles in each community activity could justify the need for increased and improved recreational activities to enhance the QOL of older people.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 60.9% of staff members in this survey thought that it is necessary to restrict the activity of children with epilepsy. Another survey indicated that attitudes towards the participation of children with epilepsy in physical activities are particularly negative, as such children have often been advised against participating in sports and exercise out of fear, over protection, and ignorance [29]. Having a better attitude towards epilepsy may be related to exposure, as staff who had acquaintances who had experienced seizures were most likely to demonstrate a positive attitude towards individuals with epilepsy [20].…”
Section: Discussionmentioning
confidence: 99%